Secure inter-cloud architecture for virtual cloud computing based on hybrid IP and MPLS infrastructure solution - Iano, Yuzo, 1950- (2016)
The Next Generation Networks use MPLS protocol in the core network to provide new services that are based on MPLS IP Cloud. This article describes an evaluation of key aspects for the construction of security on MPLS IP Inter-Cloud. The aspects to be evaluated are: separation of traffic between users of MPLS Inter-Cloud, connectivity among sites of the same Cloud application, protection of core of the cloud provider and possibility of using the same plan addresses by users, provided that they are in different MPLS IP Cloud. To achieve this goal it was proposed an architecture for assessment test